2021
DOI: 10.1080/14029251.2013.868265
|View full text |Cite
|
Sign up to set email alerts
|

Darboux transformation and novel solutions for the long wave-short wave model

Abstract: Firstly, we establish the relation between the loop group method and gauge transformation method for 3 × 3 spectral problem. Some novel solutions of long wave-short wave model are obtained by Darboux transformation method. Besides, we give the analysis and classification of solution in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The complete integrability of the LWSW model ( 1)-( 2) was tested by Painlevé analysis [42]. Ling et al constructed its Darboux transformation and found a closed multi-soliton solution formula [43,44]. A class of cusp solution for the LWSW model ( 1)-( 2) was derived by using the dressing method [45].…”
Section: High-order Rational Solution In the Determinant Formmentioning
confidence: 99%
“…The complete integrability of the LWSW model ( 1)-( 2) was tested by Painlevé analysis [42]. Ling et al constructed its Darboux transformation and found a closed multi-soliton solution formula [43,44]. A class of cusp solution for the LWSW model ( 1)-( 2) was derived by using the dressing method [45].…”
Section: High-order Rational Solution In the Determinant Formmentioning
confidence: 99%
“…For the singular RH problems, we can transform it into regular RH problems by using the dressing method [33]. In the abstract, we can solve the solution of singular RH problems accurately by the Plemelj formula and dressing method [34]- [38]. However, when the reflection coefficient has multiple higher-order poles [39], the ansatz using the dressing matrix may become complex.…”
Section: The Riemann-hilbert Problemmentioning
confidence: 99%
“…The singular RHP can be transformed to a regular one by dressing method [33]. Theoretically, based on the dressing method and Plemelj formula, the solution of singular RHP can be solved exactly [34][35][36][37][38][39]. However, the ansatz for dressing matrix may be very complicated when the reflection coefficient has multiple higher-order poles [40].…”
Section: The Riemann-hilbert Problemmentioning
confidence: 99%